2022
DOI: 10.1007/s10055-022-00631-9
|View full text |Cite
|
Sign up to set email alerts
|

Digital shinrin-yoku: do nature experiences in virtual reality reduce stress and increase well-being as strongly as similar experiences in a physical forest?

Abstract: Shinrin-yoku or forest bathing refers to a therapeutic, immersive nature experience that aids to improve well-being. The goal of the current research was to compare the effects of a physical urban nature versus virtual nature experience on stress, affect, vitality, and restoration. Previous research suggested that an immersive nature experience—such as shinrin-yoku—can be beneficial for health, but direct comparisons between physical and virtual reality (VR) experiences are scarce. In the current study, fifty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 61 publications
11
47
0
Order By: Relevance
“…Third, international cooperation can be enhanced by the use of novel methods. For example, the utilization of VR can break down the spatial and temporal barriers so as to increase statistical power and further ensure research validity ( Reese et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Third, international cooperation can be enhanced by the use of novel methods. For example, the utilization of VR can break down the spatial and temporal barriers so as to increase statistical power and further ensure research validity ( Reese et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic, strokes, Psoriatic arthritis, spinal injury, brain injury, sclerosis, cerebral palsy, and aging have all been shown to benefit from virtual reality-based games in treating and curing physical and mental symptoms. 31–33 …”
Section: Methodsmentioning
confidence: 99%
“…Diabetic, strokes, Psoriatic arthritis, spinal injury, brain injury, sclerosis, cerebral palsy, and aging have all been shown to benefit from virtual reality-based games in treating and curing physical and mental symptoms. [31][32][33] Data Analysis SPSS-23 and Smart-PLS 3.2.9 software were used to analyze the data. 34 Univariate, bivariate, and multivariate statistical analyses were performed.…”
Section: Virtual Reality Fitness and Overall Wellbeingmentioning
confidence: 99%
“…Another experimental study has shown that nature exposure can have restorative and positive mood effects both in outdoor environment and its 360-degree virtual reality video counterpart compared to an indoor control group, despite the increase in positive mood is observed only in the outdoor condition ( Browning et al, 2020a ). According to Reese et al (2022) the increase of positive and reduction of negative affect after forest bathing takes place both in a physical and simulated environment, despite a larger size effect in the physical environment. Consistently, Chirico and Gaggioli (2019) found similar emotional responses when exploring a natural landscape in real-life and through 360-degree videos.…”
Section: Introductionmentioning
confidence: 99%